Efficiency of the Compact Controlled High -Voltage Power Lines - Postolaty V.M.; Bykova E.V.; Suslov V.M.; Shakaryan Y.G.; Timashova L.V.; Kareva S.N. (Problems of the Regional Energetics)
The basic theoretical principles to create compact controlled transmission lines are analyzed in the paper. The results of technical and project elaboration of some variants of such type of power transmission lines are presented and the comparison between their technical and economic indicators with those of traditional power transmission lines and foreign analogues is made in the paper. The efficiency of compact controlled transmission lines application to form power systems and to create intersystem ties as well as distribution electric network is also stated in the paper.